PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN BANK BJB CABANG UTAMA BANDUNG - Ridwan, Mirsha Azkiya (2013)
The main issue proposed in this study is about the low performance and did not achieve the target showed by BJB Center employees. One of the factors that influence employee's performance is competence. Those competences are achievement and action competence, helping and human service competence and impact and influence competence. This study is aimed to examine several competences had by the employees. Those competence are achievement and action competence, hepling and human service competence, and impact and influence competence. Besides, it also aims to investigated the influences of those competences toward BJB Bank employees in Bandung. This study uses descriptive and verification method. It involves a population consisting 80 people as the respondents. Then, the data is analyzed by using Pearson Product Moment Coefficient Correlation and also multiple regression analysis. Hypothesis testing using the test F-test to see the influence of simultaneously and t-test to see the influence partially. The result of this study shows that achievement and action competence, helping and human service competence, impact and influence competence and employee performance of Bandung BJB Bank are categorized as medium one. There is a strong correlation between achievement and action competence with employees performance, there is a medium correlation between helping and human service competence with employees performance and there is a medium correlation between impact and influence competence with employees performance. Besides it, there is a very strong correlation among those competences. Meanwhile, the result of KD= 0,644 meaning that 64,4% employee performance is influenced by those competences, and the rest, 35,6%, is influenced by another factor which is not the main focus of this study. Key words: Achievement and Action Competence, Helping and Human Service Competence, Impact and Influence Competence, Performance